THE THINKING PROCESS OF CHILDREN WITH SPECIAL NEEDS (SLOW LEARNER) IN INCLUSION CLASSES IN SOLVING MATHEMATICAL PROBLEM - Labuem, Susana (Jurnal Pendidikan Matematika (JUPITEK), 2019)
This study aims to describe the thought process of one slow learn child in an inclusion class in solving mathematical problems structured according to Polya’s stages. This type of research is a case study. The result of this study state that in the stage of understanding the subject’s problem only remembers information at the end of the problem because of limited memory. In the stage of making a problem solving plan, the subject translate the problem into mathematical symbols based on the sequence of activities in the problem. In the stage of implementing the problem solving plan, the subject can solve existing problem but does not have confidence in the truth of the final answer obtained. In the stage of checking again, the subject does not recheck each step of completion or the final answer obtained because the subject considers the work to have been completed